PENGARUH LAMA PENYIMPANAN TERHADAP KARAKTERISTIK UMBI DAHLIA - Eko Herianto; Raswen Efendi; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Dahlia plant is one ornamental plant that has tuber with carbohydrate such as inulin. The aimed of this research to determine the effect of time storage in room temperature to dahlia tuber’s chemical contents. This research executed by experimentally using Complete Randomized Design with five treatments and three repetitionswhich followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%. The observation where with P1 (control), P2 (dahlia plant storaged in 7 days), P3 (dahlia plant storaged in 14 days), P4 (dahlia tuber storaged in 21 days), and P5 (dahlia plant storaged in 28 days). The observation result,the dahlia tuber that stored at room temperature for 28 days has lost weight 13,89%, water content 7,99%, ash content 0,53%, crude fiber3,08%, and inulin 20,54%. Mean while, sugarreduction has been increasing amount 3,58. Keywords:Inulin, dahlia tuber, time storaged.